Influence of a superdose of phytase (Optiphos) on finishing pig performance and carcass characteristics - Goodband, Robert D.; Langbein, Kari Beth; Tokach, Michael D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
A total of 1,188 finishing pigs (PIC 337 × 1050, initially 80.1 lb) were used in a 92-d experiment to determine the influence of providing phytase above that needed to meet the P requirement for growth performance and carcass characteristics. There were 27 pigs per pen and 11 pens per treatment. Each pen contained a similar number of barrows and gilts. Pens were randomly assigned to treatment based on initial BW. Basal diets contained corn, soybean meal, dried distillers grains with solubles (DDGS), and bakery meal and were formulated to meet or exceed the nutrient requirements of the pigs in each of the four phases. The four dietary treatments were formed by adding increasing levels of phytase (Optiphos 2000, Enzyvia LLC) at 0.25 (control), 0.5, 1.0 and 2.0 lb/ton. Diets were formulated such that the addition of the first 0.25 lb/ton of phytase was needed to meet the P requirement of the pigs, with further additions exceeding the P requirement. Pigs were weighed and feed disappearance was determined approximately every 14 d to determine ADG, ADFI, and F/G. On d 92, pigs were tattooed by pen number and harvested to collect carcass data. Overall (d 0 to 92), increasing dietary phytase did not influence ADG but reduced (cubic, P < 0.01) ADFI, resulting in an improvement in F/G (cubic, P < 0.01). The cubic response occurred because F/G improved as phytase inclusion increased from 0.25 to 0.5 lb/ton, with no further improvement when phytase was increased to 1.0 or 2.0 lb/ton. Phytase addition to the diet did not influence carcass measurements. These results suggest that providing phytase at levels above that needed to meet the pig’s requirement for P has the potential to improve feed efficiency.
Keywords: Finishing pig; Phosphorus; Phytase